Decreased Intraoperative Renal Tissue Oxygenation after Cardiopulmonary Bypass Predicts Cardiac Surgery-Associated Acute Kidney Injury in Neonates - Paige E. Condit; Daniel P. Gorski; Michael R. Lasarev; Awni M. Al-Subu; Matthew W. Harer (MDPI AG, 2024)
(1) Background: Near-infrared spectroscopy (NIRS) is a noninvasive tool frequently used during cardiac surgery and postoperatively in the cardiac intensive care unit to monitor regional tissue oxygen saturation. A relationship between trends of intraoperative renal oxygenation and the risk of developing cardiac surgery-associated acute kidney injury (AKI) post-operatively has not yet been established in the neonatal population. The objective of this study is to evaluate the relationship of cerebral and renal oxygenation during cardiopulmonary bypass with cardiac surgery-associated AKI in the first 72 h post-operation in neonates < 30 days of age. (2) Methods: A prospective cohort study at a tertiary care children's hospital was performed. Renal and cerebral oxygenation measured were collected intraoperatively from neonates < 30 days of age who underwent cardiopulmonary bypass for the correction of congenital heart disease. AKI was defined accordance with the Kidney Disease: Improving Global Outcomes criteria modified for neonates. Variables were compared between groups. (3) Results: 32 neonates with 35 cardiopulmonary bypass cases were included. AKI was diagnosed in 60% of cases. Intra-operative renal oxygenation, both on- and off-bypass, did not differ among the three AKI groups (p > 0.19). Renal oxygenation after coming off, but not during, cardiopulmonary bypass steadily decreased with increasing levels of AKI (Jonckheere's test, one-sided p = 0.024). (4) Conclusions: Renal oxygenation decreased in proportion to AKI severity after coming off, but not during, cardiopulmonary bypass.